Contrasting a Cassian-Merton model of mystical prayer with moments of Big-C creativity in contemporary music - Priilaid, David; Callaghan, Christian (Frontiers in Psychology, 2024)
Within the psychology literature there is a dearth in understanding how and why instances of heightened creativity, or 'Big-C', may manifest randomly, often at an early age with minimal practice and experience. In contrast to ordinary "little-c" creativity, depictions of profound creative moments and the means by which they can be attained therefore remain as enigmatic as acts of mystical prayer. Pursuing this metaphor: with little-p equating to ordinary prayer and Big-P equating to mystical prayer, from the work of St. John Cassian and Thomas Merton, we contrast the developmental path of prayer with subjective accounts of little-c and Big-C moments of creativity in the lives of famous 20 th century Anglophone artist-musicians. Here, we identify a symmetry between the aetiology of prayer and creativity. As with little-p, the development of little-c creativity is sequential, tracing a path from authenticity to task motivation, to practice and then experience. By contrast, akin to Big-P, Big-C creativity may be obtained moving from authenticity to task motivation, but thereafter circumventing the requirements of elevated practice and experience. Moreover, in moments of extreme creativity, artists manifest a profound surrender of agency as Big-C emerges spontaneously with minimal deliberate thought and an absence of ownership. Thus through Cassian-Merton we offer an historically cohesive insight on the emergence of Big-C creativity.